2020
DOI: 10.1021/acs.chemmater.9b04348
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Sodium-Doped Triphenylene Superconductors by Searching the Organic Material Database

Abstract: Over the past few decades, there has been a lot of research on organic molecule-based materials for future advanced technology. The superconductivity has also been reported in various carbon-based organic materials in line with this trend. In particular, polycyclic aromatic hydrocarbons (PAHs) have been intensively studied in recent years because of the highly conjugated characteristics of the delocalized electrons supplied by alkali metal doping. Here, we report on a PAH superconductor, sodium-doped triphenyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Modern simulation tech is a solid stool to advance the development of SCs. Yoon et al 138 innovatively applied a computational method to pick AH candidates for the SC preparation, and successfully obtained a superconductive phase of Na 3 triphenylene. A small split may be necessary between the lowest unoccupied molecular orbital (LUMO) and LUMO + 1 for the emergence of superconductivity.…”
Section: Organic Superconductorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Modern simulation tech is a solid stool to advance the development of SCs. Yoon et al 138 innovatively applied a computational method to pick AH candidates for the SC preparation, and successfully obtained a superconductive phase of Na 3 triphenylene. A small split may be necessary between the lowest unoccupied molecular orbital (LUMO) and LUMO + 1 for the emergence of superconductivity.…”
Section: Organic Superconductorsmentioning
confidence: 99%
“…(A) Energy difference Δ of 200 AH molecules from the database, (B) Stacking type of filtered molecules with Δ lower than 0.2 eV, (C) Molecular structure of final 10 candidates. Reproduced with permission: Copyright 2020, American Chemical Society 138 …”
Section: Organic Superconductorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The recrystallized samples may have lower crystallinity than the pristine sample. This is a common feature of most of doped PAHs materials [16,25,28]. Our analysis is mainly based on the position and relative strength of the major peaks.…”
Section: Crystal Structures Of Potassium Doped 23-dmnmentioning
confidence: 99%
“…The antiferromagnetic coupling in phase-pure crystal of [K(222)] 2 [p-terphenyl 3 ] that occurs in all three crystallographic directions was described by experimental results and density functional theory calculations [26]. The band structures of optimized Na 3 triphenylene crystal showed that the insertion of sodium atoms causes the material to change into metal [28].…”
Section: Introductionmentioning
confidence: 99%